Identifying the determinants of premature mortality in Russia: overcoming a methodological challenge - Leon David A; Kiryanov Nikolay; Andreev Evgueni; Shkolnikov Vladimir; Tomkins Susannah; McKee Martin; Saburova Lyudmila (BMC, 2007)
Abstract Background It is thought that excessive alcohol consumption is related to the high mortality among working age men in Russia. Moreover it has been suggested that alcohol is a key proximate driver of the very sharp fluctuations in mortality seen in this group since the mid-1980s. Designing an individual-level study suitable to address the potential acute effects of alcohol consumption on mortality in Russia has posed a challenge to epidemiologists, especially because of the need to identify factors that could underlie the rapid changes up and down in mortality rates that have been such a distinctive feature of the Russian mortality crisis. In order to address this study question which focuses on exposures acting shortly before sudden death, a cohort would be unfeasibly large and would suffer from recruitment bias. Methods Although the situation in Russia is unusual, with a very high death rate characterised by many sudden and apparently unexpected deaths in young men, the methodological problem is common to research on any cause of death where many deaths are sudden. Results We describe the development of an innovative approach that has overcome some of these challenges: a case-control study employing proxy informants and external data sources to collect information about proximate determinants of mortality. Conclusion This offers a set of principles that can be adopted by epidemiologists studying sudden and unexpected deaths in other settings.